Analisis Hubungan Activity-Based Costing dengan Peningkatan Kinerja Keuangan (Studi Empiris di Bursa Efek Jakarta) - Barbara Gunawan (Jurnal Akuntansi dan Bisnis, 2007)
This study investigates the improvement in financial performance that is associated with the use of activity-based costing (ABC), and association between ABC used and relative improvement financial performance influenced the specific enabling factors identified. One hundred and sixty internal auditors of manufacturing company in Jakarta Stock Exchange are chosen as sample. Confirmatory factor analysis and structural equation modeling are used to investigate the relationship between ABC and financial performance. The result show 1) there is no positive association between ABC use and improvement in financial performance, but there is positive association between ABC use and improvement in return on investment (ROI) when ABC and other business strategic used simultaneously, 2) the association between ABC use and relative improvement in financial performance is not influenced by specific enabling factors identified.